Language and tourism in postcolonial settings - Angelika Mietzner; Anne Storch (Bristol : Channel View Publications, 2019)
"This book focuses on perspectives from and on the global south, providing fresh data and analyses on languages in African, Caribbean, Middle-Eastern and Asian tourism contexts. It provides a critical perspective on tourism in postcolonial and neocolonial settings, explored through in-depth case studies. The volume offers a multifaceted view on how language commodifies, and is commodified in, tourism settings and considers language practices and discourse as a way of constructing identities, boundaries and places. It also reflects on academic practice and economic dynamics in a field that is characterised by social inequalities and injustice, and tourism as the world's largest industry enacting dynamic communicative, social and cultural transformations. The book will appeal to both undergraduate and postgraduate students of tourism studies, linguistics, literature, cultural history and anthropology, as well as researchers and professionals in these fields."--Back cover
Keywords: Language and culture Developing countries; Tourism Social aspects Developing countries; Sociolinguistics Developing countries; Developing countries